Upper bound limit analysis of uplift failure in pressurized sealed rock tunnels. (22nd December 2017) - Perazzelli, P.; Anagnostou, G.
Summary: The rock around tunnels used for gas storage is subject to high pressures, reaching 30 MPa in the case of compressed air energy storage. Uplift failure of the overlaying rock mass up to the surface represents the main hazard scenario in such cases. The present paper investigates this problem by using the upper bound theorem of limit analysis assuming a continuum rock mass model obeying the Mohr Coulomb failure criterion with tension cut‐off. Tools of the calculus of variations are used to assess the geometry of the failure surface. The effects of geometrical and geotechnical parameters on uplift pressure are analyzed systematically. Charts are then provided, which enable a quick estimation of the upper bound of uplift pressure across a wide range of geotechnical and geometrical conditions.